The Claustrum in Relation to Seizures and Electrical Stimulation - Kurada, Lalitha; Bayat, Arezou; Joshi, Sweta; Koubeissi, Mohamad Z. (Frontiers in Neuroanatomy, 2019)
The neural mechanisms of altered consciousness that accompanies most epileptic seizures are not known. We have reported alteration of consciousness resulting from electrical stimulation of the claustrum via a depth electrode in a woman with refractory focal epilepsy. Additionally, there are reports that suggest possible claustral involvement in focal epilepsy, including MRI findings of bilaterally increased T2 signal intensity in patients with status epilepticus. Although its cytoarchitecture and connectivity have been studied extensively, the precise role of the claustrum in consciousness processing, and, thus, its contribution to the semiology of dyscognitive seizures are still elusive. To investigate the role of the claustrum in rats, we studied the effect of high-frequency stimulation (HFS) of the claustrum on performance in the operant chamber. We also studied the inter-claustral and the claustro-hippocampal connectivity through cerebro-cerebral evoked potentials (CCEPs), and investigated the involvement of the claustrum in kainate (KA)-induced seizures. We found that HFS of the claustrum decreased the performance in the operant task in a manner that was proportional to the current intensity used. In this article, we present previously unpublished data about the effect of stimulating extra-claustral regions in the operant chamber task as a control experiment. In these animals, stimulation of the corpus callosum, the largest interhemispheric commissure, as well as the orbitofrontal cortex in the vicinity of the claustrum did not produce that same effect as with claustral stimulation. Additionally, CCEPs established the presence of effective connectivity between both claustra, as well as between the claustrum and bilateral hippocampi indicating that these connections may be part of the circuitry involved in alteration of consciousness in limbic seizures. Lastly, some seizures induced by KA injections showed an early involvement of the claustrum with later propagation to the hippocampi. Further work is needed to clarify the exact role of the claustrum in mediating alteration of consciousness during epileptic seizures.